Film adaptations of Shakespeare's 'Romeo and Juliet' - Czakó Réka; Szarvas Júlia (2002)
This thesis examines two mm adaptations of Shakespeare's 'Romeo and Juliet'. I will prove that instruments of cinematic art mean unlimited possibilities to help directors, film makers to rediscovery and revaluation of immortal literary works. Using contemporaries critics and special books, I examine Franco Zeffirelli' classical version and Baz Luhrmann's postmodern adaptation from the point of view of direction, cast, setting and costume since in my opinion these are the most determinative factors for everyday people.
Keywords: Pedagógusképzés